THEORETICAL AND METHODOLOGICAL DESCRIPTION OF THE PEDAGOGICAL ESSENCE OF THE MOTIVATIONAL APPROACH AND RELATED CONCEPTS - M. B. Artikova; D. N. Iminova (Modern American Journals, 2025)
This article provides a theoretical and methodological overview of the pedagogical essence of the motivational approach and related concepts. It emphasizes the role of motivation as a key driving force in shaping students’ academic engagement, learning behavior, and internal drive for self-development. Drawing from various pedagogical, psychological, and philosophical sources, the study explores the definition of motivation, the reasons for using a motivational approach in education, and its influence on the student-teacher interaction. The motivational approach is presented as a strategic pedagogical method that enhances the effectiveness of teaching by encouraging long-term interest, cognitive activity, and personal growth among students. The article concludes that stable and well-structured motivational processes are essential for achieving high-quality educational outcomes.
Keywords: Motivation, motivational approach, pedagogical theory, academic engagement, internal drive, learning behavior, educational process, student-teacher interaction, cognitive activity, personal development